Islam dan Menstrual Taboo - Mu'afiah, Evi (Musawa Jurnal Studi Gender dan Islam, 2007)
Menstrual taboo has been historically conceptualizedby most societies as a curse for women. Such concept of menstruation deteriorates the social position and status of women in community. This article aims to discuss how Islam deals with the menstrual taboo. This is important, because all the ideas permeates by the menstrual taboo influence they way people deal with their women through the development of frame of thought, value system as well as behavioral system. Islam states that the misogynist myth of menstrual taboo and negative view toward menstruating women is contradictory to Islamic values which respect the equality of men and women before God. Unlike the doctrines believed in other religions which say that menstruation is a symbolic curse for women because of mother Eve's mistake, Islam considers it is a natural function decreed by God to maintain the life of human race.